A reassessment of the distinctiveness of dryopithecine genera from the Iberian Miocene based on enamel-dentine junction geometric morphometric analyses. Issue 177 (April 2023) - Zanolli, Clément; Bouchet, Florian; Fortuny, Josep; Bernardini, Federico; Tuniz, Claudio; Alba, David M.
Abstract: A vast diversity of catarrhines primates has been uncovered in the Middle to Late Miocene (12.5–9.6 Ma) of the Vallès-Penedès Basin (northeastern Spain), including several hominid species ( Pierolapithecus catalaunicus, Anoiapithecus brevirostris, Dryopithecus fontani, Hispanopithecus laietanus, and Hispanopithecus crusafonti ) plus some remains attributed to ' Sivapithecus ' occidentalis (of uncertain taxonomic validity). However, Pierolapithecus and Anoiapithecus have also been considered junior synonyms of Dryopithecus by some authors, which entail a lower generic diversity and an inflated intrageneric variation of the latter genus. Since the distinction of these taxa partly relies on dental features, the detailed and quantitative analysis of tooth shape might help disentangling the taxonomic diversity of these Miocene hominids. Using diffeomorphic surface matching and three-dimensional geometric morphometrics, we investigate the enamel-dentine junction shape (which is a reliable taxonomic proxy) of these Miocene hominids, with the aim of investigating their degree of intra- and intergeneric variation compared with that of extant great ape genera. We conducted statistical analyses, including between-group principal component analyses, canonical variate analyses, and permutation tests, to investigate whether the individual and combined (i.e., Dryopithecus s.l.) variation of the extinct genera exceeds that of the extant great apes. Our results indicate that Pierolapithecus, Anoiapithecus, Dryopithecus, and Hispanopithecus show morphological differences of enamel-dentine junction shape relative to the extant great apes that are consistent with their attribution to different genera. Specifically, the variation displayed by the Middle Miocene taxa combined exceeds that of extant great ape genera, thus undermining the single-genus hypothesis. ' Sivapithecus ' occidentalis specimens fall close to Dryopithecus but in the absence of well-preserved comparable teeth for Pierolapithecus and Anoiapithecus, their taxonomic attribution remains uncertain. Among the Hispanopithecus sample, IPS1802 from Can Llobateres stands out and might either be an outlier in terms of morphology, or represent another dryopithecine taxon.